A natureza do espaço urbano: formação e transformação de territórios na cidade contemporânea - Erika Jorge Rodrigues da Cunha (2008)
This research is dedicated to investigate the urban space from the process of formation and transformation in citys occidental territories on a historic way until the contemporary. The main goal is to study the crisis that happened between the Middle Age and Modern Age. This crisis, according to Lewis Mumford and Henri Lefèbvre, may cause the lost of the human orientation to produce the urban spaces. The research explores the XVI century and the social and spatial consequences that determinate the formation of territories at city. Despite this, it was rejected the idea of the lost of human orientation to produce, therefore, it was revealed the shrink of an effort to comprehend the cities at contemporary. At the same time, the multiplication of time and space creates new life styles that impose the urban geografhy on history.